2022
DOI: 10.52547/ijrr.20.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effective field size characteristics for small megavoltage photon beam dosimetry

H. Keivan,
R. Maskani,
D. Shahbazi-Gahrouei
et al.

Abstract: Background: Small photon beams are increasingly used in modern radiotherapy modalities. In small photon fields, the dosimetric field size will deviate from the nominal field size. An effective field size (FSeff) for use in small field dosimetry has been defined to overcome this issue. The present study aims to investigate the suitability of two ionization chambers and two semiconductor diodes in the measurement of 6MV photon beam profiles and to analyze the variations of FSeff in smaller fields. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This shows the possibility of replacing diodes as semiconductor dosimeters. PDD trends in TlBr and thimble chambers were not significantly different, including the need for correction factors for sensitive volume and energy dependence of the dosimeter [18].…”
Section: Discussionmentioning
confidence: 90%
“…This shows the possibility of replacing diodes as semiconductor dosimeters. PDD trends in TlBr and thimble chambers were not significantly different, including the need for correction factors for sensitive volume and energy dependence of the dosimeter [18].…”
Section: Discussionmentioning
confidence: 90%
“…There was no significant difference in the PDD results compared with the thimble chamber, although PDD was relatively high after a depth of 5 cm. This reflects the need for a correction factor for the sensitive volume and energy dependence of the dosimeter [16]. In the case of surface dose, the difference from the thimble chamber at 0.1 cm was approximately 1.62% at 6 MV and 8.67% at 15 MV.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One of the important tasks in small field dosimetry is the determination of ROFs. It has been shown that detector-specific output correction factors , , depend on many factors such as the perturbation of particle fluence and volume averaging effects, in particular, on the field size, detector type, and the design, size, and non-water equivalency of most of the detectors [16]- [18].…”
Section: Introductionmentioning
confidence: 99%